Breaking barriers: Evaluating an arts-based emotion regulation training in prison. (February 2015) - Koch, Sabine C.; Ostermann, Thomas; Steinhage, Anna; Kende, Philip; Haller, Karl; Chyle, Fabian
Highlights: Movement and drama therapy-based anti-violence and emotion regulation program for forensic contexts. Multi-method study using self-report questionnaires, computer-based testing, focus groups, and movement observation. No difference between training group and control group on the pre-/post-anger and aggression self-report scales. Significant increase in training groups' body awareness, social competence, distance from own aggression, closeness to group and trainer; significant decrease of training groups' immediate aggression potential and increase in expression of needs (rhythms analysis). Changes in perspective taking, emotion recognition, and empathy reported in focus groups. Abstract: Creative arts therapies have long made use of the interconnection between body, emotion, and mind. Movement is intimately intertwined with emotional and cognitive functions, and role play promotes perspective taking, empathy, and interactive competencies. In this pilot study, with a pre-/post-test waiting-group design of male prison inmates in three German prisons ( n = 47), we conducted an evaluation of the movement- and drama-therapy based, anti-violence training e|m|o processing® (Lutz, 2008). The training is an action-oriented and neuroscience informed method, including movement therapy interventions for handling rage and promoting respectful interaction by means of Aikido stick fighting practice, perspective taking, and enactments. Upon completion of the training, the experimental group reported an increase in body awareness and social competence, experienced distance to their own aggression, and experienced a higher degree of closeness to the group and trainer. No changes occurred on anger and on explicit as well as implicit aggression measures. Movement analysis from behavior observations indicated a decreased immediate aggression potential and an increase in expression of needs upon termination of the training. Statements from focus groups after the training indicated improved empathy, respect, and perspective taking, both among participants and in relation to victims.